Enhanced 3-Hydroxypropionic Acid Production From Acetate via the Malonyl-CoA Pathway in Corynebacterium glutamicum - Chang, Zhishuai; Dai, Wei; Mao, Yufeng; Cui, Zhenzhen; Zhang, Zhidan; Wang, Zhiwen; Ma, Hongwu; Chen, Tao (Frontiers in Bioengineering and Biotechnology, 2022)
Acetate is an economical and environmental-friendly alternative carbon source. Herein, the potential of harnessing Corynebacterium glutamicum as a host to produce 3-hydroxypropionic acid (3-HP) from acetate was explored. First, the expression level of malonyl-CoA reductase from Chloroflexus aurantiacus was optimized through several strategies, strain Cgz2/sod-N-C* showed an MCR enzyme activity of 63 nmol/mg/min and a 3-HP titer of 0.66 g/L in flasks. Next, the expression of citrate synthase in Cgz2/sod-N-C* was weakened to reduce the acetyl-CoA consumption in TCA cycle, and the resulting strain Cgz12/sod-N-C* produced 2.39 g/L 3-HP from 9.32 g/L acetate. However, the subsequent deregulation of the expression of acetyl-CoA carboxylase genes in Cgz12/sod-N-C* resulted in an increased accumulation of intracellular fatty acids instead of 3-HP. Accordingly, cerulenin was used to inhibit fatty acid synthesis in Cgz14/sod-N-C*, and its 3-HP titer was further increased to 4.26 g/L with a yield of 0.50 g 3-HP/g-acetate. Finally, the engineered strain accumulated 17.1 g/L 3-HP in bioreactor without cerulenin addition, representing the highest titer achieved using acetate as substrate. The results demonstrated that Corynebacterium glutamicum is a promising host for 3-HP production from acetate.